2023
DOI: 10.1021/acs.jctc.3c00558
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Density Functional Theory Methods for Metalloenzyme Reactions: The Introduction of the MME55 Set

Dominique A. Wappett,
Lars Goerigk

Abstract: We present a new benchmark set of metalloenzyme model reaction energies and barrier heights that we call MME55. The set contains 10 different enzymes, representing eight transition metals, both open and closed shell systems, and system sizes of up to 116 atoms. We use four DLPNO–CCSD(T)-based approaches to calculate reference values against which we then benchmark the performance of a range of density functional approximations with and without dispersion corrections. Dispersion corrections improve the results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 193 publications
0
14
0
Order By: Relevance
“…While we do not consider these lower-level approaches as potential benchmark strategies in the subsequent DFA tests, they are useful for observing trends across the REs and BHs with the T CutPNO values, and the CBS­(2,3) results allow us to compare CPS­(6,7) to the tightened value of T CutPNO = 10 –8 , which could not be done for CBS­(3,4) as the def2-QZVPP calculations were computationally too expensive. We also note that the CPS­(5,6) and TightPNO results at the CBS­(3,4) level for the metalloenzymes CDO, Hc, and NiSOD have been taken from the brief tests we conducted when selecting the reference values for our new MME55 set, where CPS­(5,6) was referred to as “estimated TightPNO”.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…While we do not consider these lower-level approaches as potential benchmark strategies in the subsequent DFA tests, they are useful for observing trends across the REs and BHs with the T CutPNO values, and the CBS­(2,3) results allow us to compare CPS­(6,7) to the tightened value of T CutPNO = 10 –8 , which could not be done for CBS­(3,4) as the def2-QZVPP calculations were computationally too expensive. We also note that the CPS­(5,6) and TightPNO results at the CBS­(3,4) level for the metalloenzymes CDO, Hc, and NiSOD have been taken from the brief tests we conducted when selecting the reference values for our new MME55 set, where CPS­(5,6) was referred to as “estimated TightPNO”.…”
Section: Resultsmentioning
confidence: 97%
“…DLPNO–CCSD­(T)/TightPNO is regularly used to calculate reference values in benchmark studies of both organic and organometallic systems, including our work on models of enzymatically catalyzed reactions. Recent work has shown that the efficiency and accuracy of TightPNO calculations can be improved by altering the T CutPNO parameter, which determines the number of PNOs used in the correlation treatment for each electron pairPNOs with an occupation number below the threshold value are discarded. The default value of T CutPNO for TightPNO is 10 –7 , but this can be approximated with extrapolation of values calculated with T CutPNO = 10 –5 and 10 –6 (using the TightPNO default values for all other thresholds), at a significantly reduced computational cost.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations